Neuroendocrine Control, Inflammation, and Psychological Aspects After Interdisciplinary Therapy in Obese Women - Moraes, Amanda dos Santos; Cipullo, Marcos Alberto Taddeo; Poli, Vanessa Fadanelli Schoenardie; Rebelo, Renata Astride; Ribeiro, Eliane Beraldi; Oyama, Lila Missae; Silva, Stephan Garcia Andrade; Damaso, Ana Raimunda; Padovani, Ricardo da Costa; Caranti, Danielle Arisa (Hormone and Metabolic Research, 2019)
Obesity is a chronic and multifactorial disease promoted by positive energy balance. The objective was to evaluate the effects of interdisciplinary therapy in the neuroendocrine control of food intake, inflammatory markers, and psychological aspects in obese women. Forty-seven obese women (43.32±5.82 years, 34.86±3.08 kg/m2), aged 30–50 years, participated in an interdisciplinary lifestyle change therapy, consisting of nutritional counseling, physical exercises, and psychological therapy for 36 weeks. After the long-term therapy, there was a decrease in body weight (Δ –5.36 kg), BMI (Δ –2.01 kg/m2), abdominal (Δ –9.09 cm), hip (Δ –5.03 cm), and thigh (Δ –5.07 cm) perimeters. There was also a significant improvement in body composition, with an increase in fat-free mass (Δ 1.60%) and reduction of body fat (Δ –3.74 kg). The therapy proposed also provided an improvement in depression scores (Δ –6.63), anxiety (Δ –4.07), body image (Δ –25.25), and binge eating (Δ –5.25). There was a significant reduction in serum levels of leptin (Δ –15.62 ng/ml). The interdisciplinary therapy was able to provide both, physical and psychological benefits in energy balance, which enables the use of this model as a feasible clinical strategy for the treatment of obesity.
Keywords: obesity; interdisciplinary therapy; hormone; neuropeptides; energy balance